Osmotic Stress and ABA Affect Immune Response and Susceptibility of Grapevine Berries to Gray Mold by Priming Polyamine Accumulation - Hatmi, Saloua; Villaume, Sandra; Trotel-Aziz, Patricia; Barka, Essaid A.; Clément, Christophe; Aziz, Aziz (Frontiers in Plant Science, 2018)
Abiotic factors inducing osmotic stress can affect plant immunity and resistance against pathogen attack. Although a number of studies have characterized grapevine responses to various forms of biotic and abiotic stresses, the relationships between osmotic stress response and susceptibility of mature berries to Botrytis cinerea still remain unknown. In this study, we investigated the effects of osmotic stress and ABA on defense responses of mature grapevine berries before and after B. cinerea infection. We focused on the possible involvement of polyamines in the interaction between osmotic stress response and susceptibility to B. cinerea. We showed that osmotic stress induced by PEG or sucrose, and exogenous ABA induce transient but low defense responses, including weak expression of PR genes and phytoalexin synthesis in mature berries. This was accompanied by an upregulation of NCED2 involved in ABA biosynthesis and a large production of free polyamines. However, osmotic stress followed by B. cinerea infection primed berries for enhanced accumulation of polyamines, but slowed down the defense responses and increased susceptibility to the pathogen. A weak increase of diamine-and polyamine-oxidase activities was also recorded in stressed berries, but declined after pathogen infection. This suggests a possible connection between increased polyamine titer and weakened defense responses in infected berries. The pretreatment of stressed berries with appropriate inhibitors of diamine- and polyamine-oxidases further increased polyamine level and greatly lowered defense responses, leading to higher susceptibility to B. cinerea. These results are consistent with the hypothesis that low polyamine oxidation can contribute at least in part to lower defense responses by increasing polyamine titer, and subsequent disease susceptibility.